AN INTERVIEW WITH STEPHEN REYNOLDS: BARRIERS TO CRITICAL THINKING - Shaughnessy, Michael (Acta Scientiae et Intellectus, 2024)
While working for the United States Air Force and the Department of Defense, one thing emphasized was the importance of thinking about a problem critically. Eight years ago, as an alternative licensure student, I listened intently as the premise of No Child Left Behind was explained to myself and other future educators. The very idea of teaching students to think critically, backed by a national directive to teach critical thinking, was inspiring. Teaching social studies in an alternative high school, I felt I had a perfect venue for inspiring students to think critically about the world in which they live.